2004
DOI: 10.1017/s0252921100152224
|View full text |Cite
|
Sign up to set email alerts
|

Accretion Flows in Magnetic Cataclysmic Variables

Abstract: ESUMENPreseiitainos los rosnltados d(' sirnulacionos quo exploran la variedad de flujos de acrecion posibles en variables cal-aclisiiiicas iiiay,iieliras (mCVs). Niiestras simulaciories evoliicionan hasta alcanzar periodos de equilibrio qne abarcaii 0.01 < /3;pir,/Porb < 0.6, y los flujos resultantes varian desde sistemas alimentados por disco en Pspin/Porb ~ 0.01 -0.1 a sistciiias alinuaitados por corrientes en Pspin/Porb ~ 0.1 -0.5 y sistemas alimentados d('sd(' un anillo ('ii el borde <'xl,ei ioi-del lobnlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Also, tomography and the phasing of the spin waves have suggested that feeding by the accretion curtains of the material from the ring (ring-fed accretion) takes place. These findings support the models of Belle et al (2002) and Norton et al (2004) for EX Hya and the simulations done by Norton et al (2004a) which have shown that for systems with the parameters of EX Hya, the accreting material forms a ring at the outer edge of the primary Roche lobe, from where accretion curtains funnel down to the white dwarf surface.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Also, tomography and the phasing of the spin waves have suggested that feeding by the accretion curtains of the material from the ring (ring-fed accretion) takes place. These findings support the models of Belle et al (2002) and Norton et al (2004) for EX Hya and the simulations done by Norton et al (2004a) which have shown that for systems with the parameters of EX Hya, the accreting material forms a ring at the outer edge of the primary Roche lobe, from where accretion curtains funnel down to the white dwarf surface.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Norton et al (2004Norton et al ( , 2004a have shown that for systems with P spin /P orb ∼ 0.72, when the mass ratio is smaller at q = 0.2, the material forms a ring near the edge of the primary Roche lobe, from where accretion curtains funnel down to the white dwarf surface, in agreement with King & Wynn (1999) and Belle et al (2002). The material is fed from the ring (ring-fed accretion) and channeled along the magnetic field lines (when the angle between the white dwarf spin axis and magnetic dipole axis is small i.e < 30 • , which is true for EX Hya).…”
Section: Discussion Of the Orbital And Spin Datamentioning
confidence: 99%
“…The material attaches to the field lines and is channelled on to the WD’s magnetic poles, where it undergoes a strong shock. Thereafter, it settles on the surface and cools by the emission of X‐ray bremsstrahlung and optical/infrared cyclotron (Rosen, Mason & Cordova 1988; Norton et al 2004a). As proposed by Evans & Hellier (2004), most likely the prominent double‐peaked modulation in the soft X‐ray emission is due to the changing viewing geometry on to the accreting polar caps.…”
Section: Discussionmentioning
confidence: 99%